2018
DOI: 10.1002/marc.201800349
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Healing Dielectric Supramolecular Elastomer Functionalized with Aniline Tetramer

Abstract: A new design strategy to produce a supramolecular elastomer with self‐healing and dielectric properties by synthesizing an aniline tetramer (AT)‐functionalized supramolecular elastomer (SE‐AT) is demonstrated. The termination of AT in the supramolecular system not only shortens linear amide molecular chain to decrease glass transition temperature but also destroys the crystallization to achieve amorphous structure. The SE‐AT provides two kinds of noncovalent bonding including π–π stacking and the hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Li et al 69 developed highly stretchable and autonomous self-healing materials using dynamic metal-ligand interactions. When a square-wave field of >17.2 MV m À1 was applied to the self-healing dielectric elastomer actuator after the introduction of mechanical damage, an area expansion of 3.6% was achieved, thereby indicating the excellent self-healing ability of the material at temperatures as low as À20 C. Liu et al 71 produced a self-healing dielectric supramolecular elastomer functionalized with aniline tetramer. The maximum actuation strain increased with an increase of aniline tetramer content, for example, a healed elastomer with 15% aniline tetramer showed an area expansion of 4% at 9 MV m À1 at the location of the mechanical damage.…”
Section: Self-healing Dielectrics For Actuatorsmentioning
confidence: 99%
“…Li et al 69 developed highly stretchable and autonomous self-healing materials using dynamic metal-ligand interactions. When a square-wave field of >17.2 MV m À1 was applied to the self-healing dielectric elastomer actuator after the introduction of mechanical damage, an area expansion of 3.6% was achieved, thereby indicating the excellent self-healing ability of the material at temperatures as low as À20 C. Liu et al 71 produced a self-healing dielectric supramolecular elastomer functionalized with aniline tetramer. The maximum actuation strain increased with an increase of aniline tetramer content, for example, a healed elastomer with 15% aniline tetramer showed an area expansion of 4% at 9 MV m À1 at the location of the mechanical damage.…”
Section: Self-healing Dielectrics For Actuatorsmentioning
confidence: 99%
“…[15] Liu et al reported a supramolecular elastomer that self-healed with & ~ 64 -4126, Y ~ 12 -400 kPa, and relatively low E b ~ 1.1 -9.5 kV mm -1 and demonstrated self-healing of mechanical damage in a dielectric elastomer, however, the high dielectric loss (tan d) is a potential concern for device performance. [16] Finally, self-healing of mechanical and electrical damage was reported in hydrogen-bonded supramolecular polymer nanocomposites based on surface functionalised boron nitride nanosheets. [17] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of dynamic covalent bonds, such as Diels–Alder interactions, disulphide, or imine bonds, , allows the polymer chains to break and reform during thermal treatment. The introduction of supramolecular interactions, such as hydrogen bonding, ionic bonding, π–π stacking, , or metal–ligand coordination, , into polymer structures can also assist the self-healing process because of the reversible and reformative nature of the noncovalent interactions. The bond strength of the noncovalent interactions affects the self-healing dynamics and kinetics, where supramolecular interactions are also affected by phase segregation, crystallization, and chain entanglement .…”
Section: Introductionmentioning
confidence: 99%